2018
DOI: 10.1093/nar/gky227
|View full text |Cite
|
Sign up to set email alerts
|

The DNA damage response activates HPV16 late gene expression at the level of RNA processing

Abstract: We show that the alkylating cancer drug melphalan activated the DNA damage response and induced human papillomavirus type 16 (HPV16) late gene expression in an ATM- and Chk1/2-dependent manner. Activation of HPV16 late gene expression included inhibition of the HPV16 early polyadenylation signal that resulted in read-through into the late region of HPV16. This was followed by activation of the exclusively late, HPV16 splice sites SD3632 and SA5639 and production of spliced late L1 mRNAs. Altered HPV16 mRNA pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 59 publications
0
50
0
Order By: Relevance
“…Furthermore, it has been recently shown that the cellular DDR interacts with RNA processing factors [ 57 , 58 , 59 , 60 ] and that the cellular DDR affects alternative splicing of cellular mRNAs [ 61 , 62 , 63 , 64 ]. To test the idea that the DDR contributes to HPV late gene expression, we used reporter cell line C33A2 that is designed to study induction of HPV16 late gene expression to investigate if the DNA damage response could activate HPV16 late gene expression [ 53 , 65 , 66 ]. Addition of the DNA damaging agent melphalan to this reporter cell line efficiently induced the DNA damage response in the C33A2 cells, and efficiently activated the HPV16 late L1 and L2 gene expression [ 66 ].…”
Section: Human Papillomavirus (Hpv) and The Cellular Dna Damage Rementioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, it has been recently shown that the cellular DDR interacts with RNA processing factors [ 57 , 58 , 59 , 60 ] and that the cellular DDR affects alternative splicing of cellular mRNAs [ 61 , 62 , 63 , 64 ]. To test the idea that the DDR contributes to HPV late gene expression, we used reporter cell line C33A2 that is designed to study induction of HPV16 late gene expression to investigate if the DNA damage response could activate HPV16 late gene expression [ 53 , 65 , 66 ]. Addition of the DNA damaging agent melphalan to this reporter cell line efficiently induced the DNA damage response in the C33A2 cells, and efficiently activated the HPV16 late L1 and L2 gene expression [ 66 ].…”
Section: Human Papillomavirus (Hpv) and The Cellular Dna Damage Rementioning
confidence: 99%
“…To test the idea that the DDR contributes to HPV late gene expression, we used reporter cell line C33A2 that is designed to study induction of HPV16 late gene expression to investigate if the DNA damage response could activate HPV16 late gene expression [ 53 , 65 , 66 ]. Addition of the DNA damaging agent melphalan to this reporter cell line efficiently induced the DNA damage response in the C33A2 cells, and efficiently activated the HPV16 late L1 and L2 gene expression [ 66 ]. We observed a several hundred-fold induction of HPV16 L1 and L2 mRNAs as a result of inhibition of HPV16 early polyadenylation and activation of HPV16 L1 mRNA splicing, while the effect at the level of transcription was relatively modest [ 66 ].…”
Section: Human Papillomavirus (Hpv) and The Cellular Dna Damage Rementioning
confidence: 99%
See 1 more Smart Citation
“…ATM has been shown to inhibit the demethylase KDM2A, which removes di-methyl groups from H3K36, and also negatively impacts KDM4A levels through proteasome-dependent degradation [ 65 , 66 ]. Interestingly, a recent study using integrated subgenomic HPV16 reporters demonstrated that exogenously-induced DNA damage leads to production of spliced late L1 mRNAs, specifically the E1^E4^L1RNA, in an ATM-dependent manner [ 67 ]. ATM activation is required for productive replication of HPV31 [ 27 ], though whether ATM contributes to the viral life cycle through epigenetic modifications on viral chromatin is unknown.…”
Section: Resultsmentioning
confidence: 99%
“…ATM has been recently shown to affect the splicing of late mRNAs expressed from integrated HPV16 subgenomic reporter plasmids, which is postulated to occur through phosphorylation of BRCA1 and the recruitment of splicing factors to viral RNAs [ 67 ]. Our studies suggest that ATM activity regulates splicing of late L1 RNAs expressed from HPV31 episomes through the maintenance of H3K36me3 on viral chromatin.…”
Section: Discussionmentioning
confidence: 99%